2023
DOI: 10.1101/2023.05.31.542897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell type analysis of wing premotor circuits in the ventral nerve cord ofDrosophila melanogaster

Abstract: To perform most behaviors, animals must send commands from higher-order processing centers in the brain to premotor circuits that reside in ganglia distinct from the brain, such as the mammalian spinal cord or insect ventral nerve cord. How these circuits are functionally organized to generate the great diversity of animal behavior remains unclear. An important first step in unraveling the organization of premotor circuits is to identify their constituent cell types and create tools to monitor and manipulate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 205 publications
(164 reference statements)
0
26
0
Order By: Relevance
“…Wing and haltere MNs. To determine the target muscle for wing and haltere MNs, we matched the MN dendrite morphology in MANC to light microscopy image volumes of MNs with known muscle targets (Ehrhardt et al, 2023), or for three MNs identified their muscle targets in new or (basalar, b1-3; first axillary, i1, i2; third axillary, iii1, iii3, iii4; fourth axillary, hg1-4), and indirect control muscles (tergopleural,tp;pleurosternal,ps1,ps2;tergotrochanteral,TTM). The hg2 muscle in the lateral view, and the power muscles and TTM in the medial view are omitted for clarity.…”
Section: Identification Of Motor Neuronsmentioning
confidence: 99%
“…Wing and haltere MNs. To determine the target muscle for wing and haltere MNs, we matched the MN dendrite morphology in MANC to light microscopy image volumes of MNs with known muscle targets (Ehrhardt et al, 2023), or for three MNs identified their muscle targets in new or (basalar, b1-3; first axillary, i1, i2; third axillary, iii1, iii3, iii4; fourth axillary, hg1-4), and indirect control muscles (tergopleural,tp;pleurosternal,ps1,ps2;tergotrochanteral,TTM). The hg2 muscle in the lateral view, and the power muscles and TTM in the medial view are omitted for clarity.…”
Section: Identification Of Motor Neuronsmentioning
confidence: 99%
“…Table 1. Finally, in cases where cell types described here resemble those targeted in a recently published collection of split-GAL4 reagents targeting wing neurons 56 , we note the possible matches in Sup. Table 1.…”
Section: Em-lm Neuron Matching and Neuron Namingmentioning
confidence: 73%
“…Electrical recordings from possible tp1 and tp2 muscles suggest that they are active during the wing stroke of pulse and sine song ( 37 ; called b3 and b4). tp2 motor neuron silencing phenotypes are currently inconsistent across studies 39,56 , but silencing the tpn motor neurons was shown to abolish pulse and sine song 39 . There are no direct connections from the core song circuit to tp2, but tp1 and tpn are weakly innervated by TN1A and dMS2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results above (Fig. 3) will now allow us to select more specific driver lines, expressing only in the identified wing steering MNs (Ehrhardt et al, 2023), which may yield FoxP knock-out flies (or any other manipulation) with sufficient flight performance.…”
Section: Resultsmentioning
confidence: 93%